PERMANENT VASCULAR ACCESS ON THE FOREARM FOR HEMODIALYSIS IN PATIENTS WITH END-STAGE CHRONIC KIDNEY DISEASE - Роман Владимирович Султанов; Александр Андреевич Садовский; Вадим Гельевич Мозес; Кира Борисовна Мозес; Светлана Ивановна Елгина; Елена Владимировна Рудаева; Яэль Центер; Иван Александрович Кузьменко (Медицина в Кузбассе)
The analysis of the outcomes of 23 surgical interventions for the formation of AV grafts in patients with end-stage chronic renal failure using synthetic prostheses (Venoflow) (n = 10), vascular xenobioprostheses «KemAngioprosthesis» (cattle artery structured with 5 % diepoxide solution, n = 9) and translocated v. saphena magna (n = 4), performed for the period 2018-2021.